Microstructural changes and the effect on myofibril proteins in yamu (Brycon amazonicus) fish meat during cold storage (2016)
This study aimed to evaluate the effect of cold storage on yamu fish meat (Brycon amazonicus). The methodology consisted of analyzing two temperatures (0}1.6°C and -8}1°C), two storage periods (13 and 61 hours) and two different sources (farm and river), and determine changes in the protein profile, microstructural, physical and chemical properties (water retention capacity-WRC, pH, texture of yamu meat fillets). The microstructural changes were observed with optical and scanning electron microscopy. The results of the image analysis of the meat microstructure showed a negative effect from cold storage on the muscle, affecting the connective tissue. Otherwise, the analysis of protein profile demonstrated protein degradation during the cold storage of the yamu meat, such as for heavy chain myosin, actin and α-actinin. In addition, the origin of the fish and the storage temperature had a significant effect on the texture changes (P≤0.05); meanwhile, the storage time had a significant effect on the three technological characteristics of the meat (WRC, pH and texture) (P≤0.05). The storage temperature did not significantly affect the WRC (P0.05).